Artificial Intelligence diagnostics as Hospital's flagship service - El Khair Riat; Aini Qurratul (BIO Web of Conferences)
This article presents the results of a bibliometric analysis of artificial intelligence diagnostics studies that made use of the VOSviewer database and Scopus-indexed articles. The paper delves into various aspects from 2010 to 2023. Data was collected by doing searches in the Scopus database using appropriate keywords, such as “information technology” and “artificial intelligence” and “health care”. Subsequently, the collected dataset underwent meticulous analysis and visualization using the VOSviewer software. The most fruitful affiliation or institutional source for artificial intelligence diagnostics is Harvard Medical School. The writers with the most are Abelha, A. and Machado, J. The United States is the nation that produces the greatest amount of scientific articles related to artificial intelligence diagnostics. The most important journal for artificial intelligence diagnostics is International Journal of Medical Informatics. The most common subjects in artificial intelligence diagnostics is medicine. With ninety-five publications, the number of international scholarly publications on artificial intelligence diagnostics reached a peak in 2023. Sixty-nine writers are closely associated with the ownership of two or more documents. There are 388 keywords with strong relationships by selecting with a minimum of 5 occurrences. The findings provide valuable insights into the dynamics and characteristics of artificial intelligence diagnostics research.